Efeitos de diferentes materiais restauradores na formação de biofilme: análise do ângulo de contato, rugosidade da superfície 3d e microscopia confocal - Almeida, Juliana Silvério Flausino de (2013)
The purpose of this study was to evaluate the effect of the topography parameters and hydrophobicity of restorative material used to restore non-carious cervical lesions on the biofilm formation. Four restorative materials were investigated: conventional glass ionomer cement (KF, Ketac Fill Plus, 3M ESPE), resin-modified glass ionomer cement (VT, Vitremer, 3M ESPE), nanofilled resin-modified glass ionomer (KN, Ketac Nano, 3M ESPE) nanofilled resin composite (FZ, Filtek Z350 XT, 3M ESPE). Forty disk specimens were prepared from each material, dived in four groups. Five samples were used for topography parameters analysis using a 3D profilometry. The amplitude parameters (Sa and Sq), spatial parameter (Sds) and hybrid parameter (Ssc) were extracted in area using cut off of 0.25mm. Hydrophobicity was determined by the contact angle measurement of deionized water on the surface. Biofilm was evaluated after 24 hours formation with each disk after stained with 1% fluorescein using confocal laser-scanning microscopy (CLSM). Data were analyzed using one-way ANOVA and Tukey test (α=.05), Pearson correlation was used to compare topography parameters with biofilm formation. Significant differences were found related amplitude parameters (Sa and Sq, FZ=KN˂VT˂KF). KN presented the highest hydrophobicity. FZ and KN presented the lowest thickness and biovolume of biofilm when compared with VT and KF. All topography parameters were significantly correlated with biofilm formation. FZ and KN, material with nanoparticles presented better performance related topography parameters and biofilm formation.